Protolith Oceanic Island Arc dari Granitoid Tipe M dan I di Karangsambung, Kebumen, Jawa Tengah - Chusni Ansori; Shaban Godang; Defry Hastria; Isyqi isyqi (Pusat Survei Geologi, 2019)
Granitoid rocks which found at Luk Ulo melange complex as rock fragments with pale gray colour and faneritic texture. Petrogenesis and geotectonic of the granitoid is under debate. Some geologists consider as plagiogranite, which is formed from the Mid Ocean-ridge (MOR); or leucogranite which is formed from continental collision, and others argue as arc-related granitoid type.The field studies ware carried out on 5 (five) tracks around Luk Ulo River and 1 (one) track at Lokidang River. The pale grey Karangsambung granitoid is composed of the mainly K-feldspar (34-55%), plagioclase (10-25%) and quartz (25-35%), and chemically contains SiO2 (61.25 - 66.06%); Al2O3 (13.94 – 14.61%), K2O (2.53 - 4.00%), Na2O (3.42 - 4.10%), CaO (2.32 - 4.76%), Fe2O3 total (5.85 – 8.71%), MgO (0.98 – 1.97%). The granitoid is M- and I-type that were formed at 760o - 800o C with a depth of about 20-30 km, resulting from the differentiation of magma from a fragment origin of the K-enriched oceanic island arc originating from drifting of the IAB fragment. The sample of basalt 17D has a relatively high of Nb/Ta ratio (20), low Rb (<2 ppm), low Ba (17 ppm), and is interpreted as interacting with MORB mantle magma containing rutile-melt;whereas quartz monzonite (17A) has a relatively low of Zr/Sm ratio (3.86), which is indicated to have been contaminated by a carbonatite magma. The spidergram pattern of mantle metagabbro (sample no. 13) similar with the basalt from IAB-Bransfield Strait (Antarctica). Results of a comprehensive geochemical study proposes that the current condition of the Karangsambung zone is part of geotectonic of ACM-Eurasia, that composed of a combination of four rock fragments, i.e. (a) the rocks which sourced from IAB fragments, (b) mantle MORB, (c) continental crust from the origin of ACM-Eurasia, (d) the origin fragment from carbonatite magma.Keyword: Luk Ulo Melange Complex, pale grey granitoid, Island-arc granitoid, M and I-type granitoid